Employee Performance Improvement through Strategic Human Resource Management, Burn Out and Work Ability with Intention to Leave as Intervening Variable on PT. Susanti Megah, Surabaya - Vivin Tri Astuti; Siti Mujanah; Sumiati (PT Inovasi Pratama Internasional, 2023)
Human resource management is currently focused on Strategic Human resource Management, which includes strategic practices of Human resource management while also considering other variables to build employee performance in a company. Therefore, this study aims to examine the influence of Strategic Human resource management, Burnout, and Work Ability on Employee performance, with Intention to Leave as an intervening variable, at PT. Susanti Megah, Surabaya. This study is quantitative research with an explanatory approach, using a questionnaire as the primary data source. The questionnaire was distributed to 150 employees of PT. Susanti Megah, Surabaya. The calculation and data analysis used for hypothesis testing in this study employed Smart-PLS 3.2 software. The results of the study show that Strategic Human Resources Management has a negative but non-significant effect on Intention to leave but a positive and significant effect on Employee Performance. Burnout has a positive and significant effect on the intention to Leave, but it also has a negative and significant effect on Employee Performance. Work Ability has a negative and significant effect on the intention to Leave, but it also has a positive and significant effect on Employee Performance. The intention to Leave has a negative and significant effect on Employee Performance.